Hotspot wireless LANs to enhance the performance of 3G and beyond cellular networks. - Doufexi, A. (IEEE Communications magazine)
At present, WLANs supporting broadband multimedia communications are being developed and deployed around the world. Standards include HIPERLAN/2 defined by ETSI BRAN and the 802.11 family defined by the IEEE. These systems provide channel adaptive data rates up to 54 Mb/s (in a 20 MHz channel spacing) over short ranges up to 200 m. The HIPERLAN/2 standard also specifies a flexible radio access network that can be used with a variety of core networks, including UMTS. It is likely that WLANs will become an important complementary technology to 3G cellular systems and will typically be used to provide hotspot coverage. In this article the complementary use of WLANs in conjunction with UMTS is presented. In order to quantify the capacity enhancement and benefits of cellular/hotspot interworking we have combined novel ray tracing, software-simulated physical layer performance results, and optimal base station deployment analysis. The study focuses on an example deployment using key lamppost mounted WLAN access points to increase the performance (in terms of capacity) of a cellular network.